Nilai Kesetaraan Gender dalam Perspektif Islam - Mutmainah, Hidayatul; Arifin, Samsul; Munir, Misbahul (TA'LIMUNA: Jurnal Pendidikan Islam, 2022)
Abstrac: In the past, many people were not interested in distinguishing sex and gender, because the perceptions that developed in society considered gender differences (differencs gender) as a result of sex differences (differencs sex), so that the division of roles and work sexually was seen as something natural. But many people in this new era misinterpret gender related positions in Islam. The nature of women which includes menstruation, pregnancy, childbirth and breastfeeding is often connected by some people with traditional stories, believed to be the truth which is commonly called a myth, even considered from the teachings of Islam. But lately it has been realized that not necessarily the sex differences cause gender inequlity. Because in Islam the equality of men and women in the presence of Allah are both servants, caliphs on earth, and accept primordial agreements